A peroxidase-like magneto-gold nanozyme AuNC@Fe3O4 with photothermal effect for induced cell apoptosis of hepatocellular carcinoma cells in vitro - Shi, Xinglong; Liu, Jifa; Wang, Guannan (Frontiers in Bioengineering and Biotechnology, 2023)
Hepatocellular carcinoma (HCC) is one of the most commonly diagnosed and malignant cancers worldwide. Conventional therapy strategies may not completely eradicate the tumor and may cause side effects during treatment. Nano-catalytic therapy, as a novel strategy, has attracted a great deal of attention. This study aimed to synthesize a multifunctional magneto-gold nanozyme AuNC@Fe3O4 and evaluate its anti-cancer potential in HepG2 cells in vitro. The characteristics of AuNC@Fe3O4 were assessed using a transmission electron microscope, dynamic light scattering, and energy-dispersive X-ray. The photothermal performance and peroxidase (POD)-like activity of AuNC@Fe3O4 were detected using thermal camera and ultraviolet-visible spectrophotometer, respectively. The anti-cancer potential of AuNC@Fe3O4 was examined using cell counting kit-8, live/dead cell staining, and apoptosis analysis. Further research on HepG2 cells included the detection of intracellular reactive oxygen species (ROS) and lysosomal impairment. We observed that the AuNC@Fe3O4 had a small size, good photothermal conversion efficiency and high POD-like activity, and also inhibited cell proliferation and enhanced cell apoptotic ability in HepG2 cells. Furthermore, the AuNC@Fe3O4 enhanced ROS production and lysosomal impairment via the synergistic effect of photothermal and nano-catalytic therapies, which induced cell death or apoptosis. Thus, the magneto-gold nanozyme AuNC@Fe3O4 may offer a potential anti-cancer strategy for HCC.